Increased occurrence of hypothyroidism among pregnant women during the first trimester and its correlation with anti-thyroid peroxidase antibody (anti-TPO) and gestational diabetes mellitus in Chattagram region, Bangladesh - Sharmen, Farjana; Sadaf, Samia; Jabin, Nowshin; Malik, Adiba; Hashem, M. A.; Ali, Yeasmeen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The present study was aimed at investigating the prevalence of hypothyroidism in pregnant women in their first trimester in Chattagram, an iodine-sufficient area in Bangladesh. We also studied whether hypothyroidism in pregnancy has any correlation with high titres of anti-thyroid peroxidase (anti-TPO) antibodies and the occurrence of gestational diabetes mellitus. Methods: Our study included 100 pregnant women at their first antenatal checkup based on certain preselected criteria in two tertiary care hospitals in Chattogram. The levels of serum TSH, FT4, and anti-TPO were estimated to detect thyroid function from the collected blood sample. The oral glucose tolerance test was carried out between 24 and 28 weeks of gestational age. A standard predesigned proforma was used to record a detailed patient history and the findings of general physical examinations. Results: According to our results, thyroid disorder and GDM affect 19% and 13% of total pregnancies, respectively. Among TD patients, subclinical hypothyroidism (SCH) prevails the most (11%). The majority of the hypothyroid patients with a high titre of anti-TPO positivity (11%) indicate an autoimmune etiology (p<0.001). Furthermore, a statistically significant relationship (p<0.01) was established between hypothyroidism and GDM. No demographic data was observed to affect GDM and hypothyroidism. Conclusion: Thyroid disorders affect one in every six pregnant women in the southern part of Bangladesh. Moreover, hypothyroid pregnant women were found to be highly susceptible to GDM. Euthyroid women with a high titre of anti-TPO during their gestation should be closely monitored for the development of hypothyroidism and GDM.